PT-VWD posing diagnostic and therapeutic challenges – small case series. (4th July 2017) - Sánchez-Luceros, Analía; Woods, Adriana I.; Bermejo, Emilse; Shukla, Shilpa; Acharya, Suchitra; Lavin, Michelle; Rydz, Natalia; Othman, Maha
Abstract: Despite the increased worldwide awareness, over the last decade, of the platelet-type von Willebrand Disease (PT-VWD), many uncertainties remain around this rare platelet bleeding disorder. This report aims to correctly identify and study the phenotype of new patients and highlights the diagnostic and therapeutic challenges this disease remains to pose. We describe four PT-VWD cases confirmed by genetic analysis in which either the diagnosis and/or the treatment posed challenge. We provide the details of the clinical presentation, laboratory analysis, and the treatment and the responses in each case. We show that in addition to type 2B VWD, PT-VWD can be misdiagnosed as idiopathic thrombocytopenic purpura, neonatal alloimmune thrombocytopenia, and unexplained gestational thrombocytopenia. The disease can be diagnosed as early as 1 year of age and with phenotypically normal parents. Bleeding in some patients can be managed successfully using Humate P and DDAVP combined with tranexamic acid with no significant thrombocytopenia. We provide for the first time an evidence of an efficient response to rFVIIa in PT-VWD. Anaphylactic reaction to VWF preparations may be related to PT-VWD and the development of HLA antibodies is not uncommon. Progressive thrombocytopenia with normal VWF levels can be seen with PT-VWD and the platelet count was normalized at 2.5 weeks postpartum in one case. We conclude that these studies represent a record of clinical observations/interventions that help improve diagnoses/management of PT-VWD, highlight the variations in age and clinical presentations, laboratory diagnostic approaches, the importance of genetic testing for accurate diagnosis and consideration of therapeutic alternatives.